Collective bargaining in Brazilian manufacturing, 1978-95 - Horn, Carlos Henrique Vasconcellos (2003)
Collective bargaining, it is widely claimed, has been on the increase in Brazil since the late 1970s. This is seen as part of a broader change in Brazilian industrial relations towards a hybrid system of interest representation, in which elements of both the old state corporatism and pluralism now coexist. However, there is little or no systematic empirical evidence available to support this conclusion. This thesis addresses the question of the strengthening of collective bargaining as a method of job regulation in Brazil by providing a detailed empirical study. The questions of this study are: (a) how important has collective bargaining become in establishing provisions on the terms and conditions of the employment relationship which are not simply reproducing rules established via state regulation?; and (b) what factors accounted for changes in the content of these provisions? An analysis of 10,734 provisions in 287 collective agreements in manufacturing industries in the Metropolitan Area of Porto Alegre, the capital of the southernmost state of Rio Grande do Sul, was carried out for the period of 1978-95. This analysis offers support for the thesis that the significance of collective bargaining has increased. It shows that: (a) most substantive provisions created rules that were not established in other forms of regulation; (b) provisions that replicate the contents of regulatory legislation accounted for one out of seven substantive provisions, but in spite of being a copy of the law, these provisions are not entirely neutral for job regulation; (c) collective agreements also laid down substantive provisions benefiting employers, and not simply employees; and (d) the pace of change in bargaining outcomes oscillated with changes in the economic, legal and judicial contexts. This pace of change was mostly affected by (i) the rate of unemployment, (ii) the degree of openness of the economy to foreign competition, (iii) the capacity of employers to pass on costs to costumers, (iv) stabilisation policies aimed at curbing inflation, (v) the Federal Constitution made in 1988, (vi) the official rate of minimum wages, and (vii) the conduct of the labour judicial system in settling collective disputes.